Efeitos da dieta rica em fibra alimentar sobre aspectos macroscópicos e microscópicos dos cólons em ratos - Fernandes, Danielle de Maria Paiva Alves (2020)
Dietary fiber consists of carbohydrate polymers ( CHO) cells which escape digestion in the small intestine and pass to the colon where there is little or almost completely fermented , providing products that contribute to many physiological benefits , directly influencing the colon and microbiome. The aim of this study was to verify the effects of fiber-rich diet on the macroscopic and microscopic properties oh the colon in rats. Were used 40 Wistar rats, males, with average weight of 250g. The rats were randomly divided into four groups, with 10 animals each. Two Control Groups (CG) received standard diet and water and two Test Groups (TG) received diet rich in mix of wheat bran and Guar gum and Hydrolyzed Inulin and water. Each group GC and GT has undergone euthanasia with three and six months of treatment with the fiber. Evaluations were conducted of the weight of the animals, macroscopic and microscopic colon properties, in the third and sixth months of the experiment. There was a significant changes in the weights of the animals. There was no significant increase in the weight of the proximal colon GT three months (ρ < 0,001). Regarding to the microscopic aspects had significant results at the time of the gland in the cecum in both groups (GT and GC), in the proximal colon of the glands increased from six months (ρ < 0,001) and distal colon there was a decrease of the glands of the GT of six months (ρ < 0,001). goblet cells in the quantification of the cecum, there was the budget amount in the GT three months (p < 0,05) and distal colon there was an increase in the number of cells of the GT three months (p < 0,001). It is therefore concluded that a diet high in fiber, changes the weight of the proximal colon transiently, but favors the cellularity and the height increase of crypts in the cecum of constant mode.